2010
DOI: 10.1111/j.1750-3841.2010.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Soluble Soybean Polysaccharides to Dairy Products as a Source of Dietary Fiber

Abstract: Increasing consumption of dietary fiber in food leads to many important health benefits: for example, reduction in blood cholesterol, reduced risk of diabetes, and improved laxation. Water soluble soybean polysaccharide (SSPS) is a dietary fiber extracted and refined from okara, a byproduct of soy manufacturing. It was incorporated into 3 categories of dairy-based products, thickened milkshake-style beverages, puddings, and low-fat ice cream, to the maximum amount without over-texturing the food. Rheological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
2
15
1
1
Order By: Relevance
“…Soukoulis et al () revealed that the flow behaviour index of ice cream containing dietary fibre was in the range of 0.45–0.84. Similarly, a decrease in the flow behaviour index was observed in several studies on ice cream mixes containing natural plant material (Soukoulis et al ; Chen et al ) and different hydrocolloids (Kaya and Tekin ; Marcotte et al . ; Razavi et al ; Soukoulis et al ; BahramParvar et al ; Javidi et al ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Soukoulis et al () revealed that the flow behaviour index of ice cream containing dietary fibre was in the range of 0.45–0.84. Similarly, a decrease in the flow behaviour index was observed in several studies on ice cream mixes containing natural plant material (Soukoulis et al ; Chen et al ) and different hydrocolloids (Kaya and Tekin ; Marcotte et al . ; Razavi et al ; Soukoulis et al ; BahramParvar et al ; Javidi et al ).…”
Section: Resultssupporting
confidence: 60%
“…Effect of pumpkin puree and guar gum on steady shear flow behaviour (a) and thixotropy (b) of ice cream mix at 5°C (P and G are pumpkin puree and guar gum, respectively). containing natural plant material(Soukoulis et al 2009;Chen et al 2010) and different hydrocolloids(Kaya and Tekin 2001;Marcotte et al 2001;Razavi et al 2007;Soukoulis et al 2008;BahramParvar et al 2010;Javidi et al 2016).…”
mentioning
confidence: 99%
“…With the exception of SL, the formulations did not differ significantly from the control (C). Those results were higher than those obtained by Chen et al (2010), who analyzed low-fat content ice creams enriched with 2%, 3%, and 4% of polysaccharides extracted from soybeans as fiber source. The average global acceptance scores in the hedonic scale varied from 5 to 6.2, but the ice creams with higher percentage of fiber obtained the lowest acceptance averages.…”
Section: Resultscontrasting
confidence: 48%
“…Ayrıca, diyet liflerin kullanım oranının da dondurma mikslerinin donma noktaları üzerine etki ettiği görülmüş, bütün lif çeşitlerinde %2'lik oranın daha etkili olduğu saptanmıştır. Bir başka çalışmada [50], diyet liflerce zengin dondurma üretimi gerçekleştirmek amacıyla çözünür soya fasulyesi polisakkaritleri (SF) farklı oranlarda (%1, 2, 3, 4) kullanılmış ve örneklerin bazı duyusal özelliklerine bakılmıştır. 102 panelist ile gerçekleştirilmiş duyusal değerlendirme sonuçlarına göre görünüş, aroma, tatlılık ve tekstür özellikleri açısından %2 SF içeren örnek en yüksek puanları almış, aynı özellikler bakımından en düşük puanları ise %4 SF içeren örnek almıştır.…”
Section: Diyet Liflerce Zenginleştirilmiş Dondurmaunclassified